El desafío del liderazgo - Kouzes, James M., 1945-; Posner, Barry Z. (BookaVivo, 2021)
First published in 1987 The Leadership Challenge is the research-based reference manual for effective leadership written by Kouzes and Posner, the leading authorities in the field. This sixth edition of the work of Kouzes and Posner is an update of the book that has become "the bible" of leadership and an international best-seller translated into more than 20 languages, with more than 2.5 million copies sold. . The Leadership Challenge is the gold standard manual for effective leadership, based on research and written by leading authorities in the field. With deep insight into the complex interpersonal dynamics of the workplace, this book positions leadership as both a skill to be learned and a relationship that must be nurtured to reach its full potential. This new sixth edition has been revised to address today's challenges, including more international examples and a laser focus on business issues; You'll learn how extraordinary leaders accomplish extraordinary things and how to develop your leadership skills and style to deliver quality results every time. Engaging stories delve into the critical roles great leaders fill, and simple frameworks provide an introduction for those seeking continuous improvement; By internalizing key insights and putting concepts into action, you'll become a more effective and impactful leader